Chronic kidney disease of unknown aetiology in Sri Lanka: is cadmium a likely cause? - Peiris-John Roshini J; Wanigasuriya Kamani P; Wickremasinghe Rajitha (BMC Nephrology, 2011)
Abstract Background The rising prevalence of chronic kidney disease (CKD) and subsequent end stage renal failure necessitating renal replacement therapy has profound consequences for affected individuals and health care resources. This community based study was conducted to identify potential predictors of microalbuminuria in a randomly selected sample of adults from the North Central Province (NCP) of Sri Lanka, where the burden of CKD is pronounced and the underlying cause still unknown. Methods Exposures to possible risk factors were determined in randomly recruited subjects (425 females and 461 males) from selected areas of the NCP of Sri Lanka using an interviewer administered questionnaire. Sulphosalicylic acid and the Light Dependent Resister microalbumin gel filtration method was used for initial screening for microalbuminuria and reconfirmed by the Micral strip test. Results Microalbumnuria was detected in 6.1% of the females and 8.5% of the males. Smoking (p < 0.001), alcohol use (p = 0.003), hypertension (p < 0.001), diabetes (p < 0.001), urinary tract infection (UTI) (p = 0.034) and consumption of water from wells in the fields (p = 0.025) were associated with microalbuminuria. In the binary logistic regression analysis, hypertension, diabetes mellitus, UTI, drinking well water in the fields, smoking and pesticide spraying were found to be significant predictors of microalbuminuria. Conclusions Hypertension, diabetes mellitus, UTI, and smoking are known risk factors for microalbuminuria. The association between microalbuminuria and consumption of well water suggests an environmental aetiology to CKD in NCP. The causative agent is yet to be identified. Investigations for cadmium as a potential causative agent needs to be initiated.